Root cause analysis of the failure of the steam generator orifice assembly of a test reactor. (November 2021) - Albert, Shaju K.; Suresh Kumar, R.; Kumar, Hemant; Nanda Kumar, R.; Toppo, Anita; Poonguzhali, A.; Elango, M.; Babu, A.
Highlights: Root cause analysis of the failure of the steam generator orifice assembly is investigated. Both metallurgical and mechanics based post-failure investigations were performed. Stress corrosion cracking (SCC) is the cause of failure. Geometrical constraint against the thermal shrinkage during welding developed residual tensile stresses and led to SCC. The design of the orifice assembly has been revised to mitigate a similar kind of failure in future. Abstract: Radiographic examination performed based on the increase in flow through one of the steam generators (SG) indicated the physical separation of orifice assembly from the orifice holder. Subsequently, this failed orifice assembly was cut from the feed water inlet header of the SG Module and subjected to further investigation. Both metallurgical and mechanics based post-failure investigations were performed. The failure of orifice assembly is attributed to stress corrosion cracking (SCC). Scanning electron microscopic (SEM) observation of the fractured surface showed an inter-granular mode of SCC failure. SCC occurred due to the residual tensile stresses developed due to the geometrical constraint against the thermal shrinkage during welding. A minimum gap of 160 µm at the top mating portion of the orifice assembly before the welding could have absorbed the thermal shrinkage to prevent the existence of sustained residual stresses and thereby SCC failure. Austenitic stainless steels are highly susceptible to SCC under the combined action of tensile stress and favourable environmental conditions. Under the favourable situation to SCC, cracks propagate slowly without any noticeable deformation until the stresses in the remaining ligament of metal exceed the fracture strength. Based on the insights gained from the root cause analysis, the design of the orifice assembly has been revised to mitigate a similar kind of failure in future.